Biomedical Informatics Computer Applications in Health Care and Biomedicine - Shortliffe, Edward H.; Cimino, James J. (Springer London : Imprint: Springer, 2014)
Biomedical Informatics: Computer Applications in Health Care and Biomedicine meets the growing demand of practitioners, researchers, educators, and students for a comprehensive introduction to key topics in the field and the underlying scientific issues that sit at the intersection of biomedical science, patient care, public health, and information technology (IT). This 4th edition reflects the remarkable changes in both computing and health care that continue to occur and the exploding interest in the role that IT must play in care coordination and the melding of genomics with innovations in clinical practice and treatment.  New chapters have been introduced on the health information infrastructure, consumer health informatics, telemedicine, translational bioinformatics, clinical research informatics, and health IT policy, while the others have all undergone extensive revisions, in many cases with new authors. The organization and philosophy are unchanged, focusing on the science of information and knowledge management and the role of computers and communications in modern biomedical research, health, and health care.  Emphasizing the conceptual basis of the field rather than technical details, it provides an introduction and extensive bibliography so that readers can comprehend, assess, and utilize biomedical informatics and health IT.  The volume focuses on easy-to-understand examples, a guide to additional literature, chapter summaries, and a comprehensive glossary with concise definitions of recurring terms for self-study or classroom use.